Laporan Kasus: Rinitis Alergi dengan Hipertrofi Adenoid - Reihana Tasya Vunna Salipu; Hastuti Rahmi; Dhinasty Armenia W (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: Allergic rhinitis is an inflammation of the nasal mucosa triggered by allergens, leading to symptoms such as sneezing, nasal congestion, and excessive nasal discharge. Adenoid hypertrophy is the enlargement of the adenoid glands in the nasopharynx, commonly occurring in children, which can result in breathing difficulties and upper respiratory infections. These two conditions often coexist in children and impact their quality of life, particularly in terms of breathing and sleep. In Indonesia, the prevalence of allergic rhinitis is estimated to be around 38%. Case Report: An 8-year-old girl patient came to the ENT clinic at RSUD Kabupaten Bekasi with the main complaint of nasal congestion for more than a week. This was accompanied by a cough, nasal discharge and itching, sore throat, sneezing, and snoring during sleep. Endoscopic examination revealed eutrophic inferior and middle turbinates, mucous secretion, and hypertrophy of the adenoid covering the torus tubarius. The patient was diagnosed with allergic rhinitis and adenoid hypertrophy and was treated with nasal corticosteroid spray, antihistamines, decongestants, expectorants, and advised to avoid allergens such as dust. Conclusion: Adenoid hypertrophy with allergic rhinitis can cause upper airway obstruction and sleep disturbances, such as obstructive sleep apnea syndrome (OSAS), which affects physical and cognitive development and requires appropriate management. Management of adenoid hypertrophy can be pharmacological or surgical, depending on the patient's clinical symptoms. Allergic rhinitis can be treated with antihistamines, nasal corticosteroid spray, and avoidance of allergens.